Highly purified fucosylated chondroitin sulfate oligomers with selective intrinsic factor Xase complex inhibition. (15th October 2019) - Yan, Lufeng; Wang, Danli; Zhu, Mengshan; Yu, Yanlei; Zhang, Fuming; Ye, Xingqian; Linhardt, Robert J.; Chen, Shiguo
Highlights: A fast preparation of fucosylated chondroitin sulfate (FCS) oligomers was reported. The FCS oligomers were well identified in structure. The FCS oligomers showed selective intrinsic factor Xase complex inhibition. The FCS oligomers showed remarkable antithrombotic activity without bleeding and hypotension. Abstract: Fucosylated chondroitin sulfate (FCS) oligosaccharides of specific molecular weight have shown potent anticoagulant activities with selectivity towards intrinsic factor Xase complex. However, the preparation of FCS oligosaccharides by traditional methods requires multiple purification steps consuming large amounts of time and significant resources. The current study focuses on developing a method for the rapid preparation of FCS oligomers from sea cucumber Pearsonothuria graeffei having 6–18 saccharide residues. The key steps controlling molecular weight ( M w) and purity of these FCS oligomers were evaluated. Structural analysis showed the resulting FCS oligomers were primarilyl -Fuc3, 4diS-α1, 3-d -GlcA-β1, 3-(d -GalNAc4, 6diS-β1, 4-[l -Fuc3, 4diS-α1, 3-]d -GlcA-β1, 3-)n d -anTal-ol4, 6diS (n = 1˜5) accompanied by partial de-fucosylation and/or de-sulfation. In vitro and in vivo experiments demonstrate that these FCS oligomers selectively inhibit intrinsic factor Xase complex and exhibit remarkable antithrombotic activity without hemorrhagic and hypotension side effects. This method is suitable for large-scale preparation of FCS oligosaccharides as clinical anticoagulants.